Pengembangan Kurikulum Bahasa Arab Pesantren Mu'adalah (Studi Kasus di Pondok Pesantren Al-Kausar Genteng Banyuwangi) - Himmah, Ro'fat Hizmatul; Amrulloh, Muhammad Afif (Universitas Islam Negeri Raden Intan Lampung, 2017)
Abstract: Pesantren curriculum as a Mu'adalah between the curriculum at educational institutions using the book and the quality criteria that have been set out in a fair and open. Therefore, this study was conducted to find out an overview of the planning, implementation and evaluation of curriculum development of Arabic at pesantren Al C. This study uses qualitative research methods, descriptive data collection techniques in the form of observation, interview and documentation as well as the use of trainggulasi resources to check the validity of the data. Based on this study, it was found that the Arabic curriculum planning at the boarding school places emphasis on the achievement of language proficiency in the aspects of speaking and reading. This is because diplomas issued synchronised with the Middle East. The book, which provided the material for the study using the book the classic form of Jurumiyah and Imrity for the Nahwu lessons. The direct method of the form sorogan. As for the evaluation of the system using the midle of the semester and semester. Thus, this study is very important to realize service and organization of education boarding schools better through the development of the curriculum based on evaluation and the development needs of the community. Keywords: Kurikulum, pesantren, mu’adalah